The relation of menarcheal age to obesity in childhood and adulthood: the Bogalusa heart study - Srinivasan Sathanur R; Dietz William H; Serdula Mary K; Khan Laura; Freedman David S; Berenson Gerald S (BMC, 2003)
Abstract Background Several studies have shown that girls who undergo menarche at a relatively young age tend to be more obese as adults. However, because childhood (pre-menarcheal) levels of weight and height are associated with an earlier menarche, the increased prevalence of adult obesity among early maturers may largely reflect the persistence of childhood obesity into adulthood. Methods We examined these interrelationships among 1179 girls (65% white, 35% black) who were examined as children (mean age, 9 y), adolescents, and adults (mean age, 26 y) in the Bogalusa Heart Study. Results Both white and black women who reported that they underwent menarche before age 12 y had, on average, higher adult levels of weight (+10 kg), body mass index (BMI, +4 kg/m2) and skinfold thicknesses (+6 mm) than did women who underwent menarche after age 13.5 y. However, relatively fat children tended to undergo menarche earlier than did thinner children, with each standard deviation increase in pre-menarcheal BMI increasing the odds of early menarche (<12 y) by approximately 2-fold. Stratified and regression analyses indicated that (1) adult obesity was more strongly associated with childhood obesity than with menarcheal age, and (2) about 60% to 75% of the apparent effect of menarcheal age was due to the influence of childhood obesity on both menarcheal age and adult obesity. Conclusions Although additional longitudinal studies are needed, it is likely that the importance of early menarche in adult obesity has been overestimated. Most of apparent influence of menarcheal age on adult obesity is attributable to the association of childhood obesity with both menarcheal age and adult obesity.